Cognitive perspectives on peer learning - O'Donnell, Angela M.; King, Alison (Rutgers invitational symposium on education series., 1999)
"The contribution of this volume to the literature on peer learning is its focus on approaches that reflect a common concern with cognitive processes based on developmental, information processing, or more generally, constructivist perspectives on peer learning. Although the clear importance of the social context of peer learning is not ignored, the volume's emphasis is on the cognitive growth that occurs within the learning environment."--BOOK JACKET. "This volume is based on original papers presented by the contributing authors in November 1996 at the Rutgers invitational Symposium on Education on Cognitive Skills and Learning With Peers."--Jacket